Application of ERCP in biliary and pancreatic diseases in children: a retrospective analysis of 4-year clinical data from a single center - Qin, Xiumin; Yu, Feihong; Guo, Hui; Zhao, Chunna; Wu, Jie (Frontiers in Pediatrics, 2026)
ObjectiveThis study aimed to summarize the clinical experience of Endoscopic Retrograde Cholangiopancreatography (ERCP) in a pediatric population, analyzing the disease spectrum, procedural characteristics, and clinical outcomes to contribute to the understanding of its application in children.MethodsThis study reviewed the clinical data of children who presented to our hospital and underwent ERCP and related procedures between January 2021 and December 2024. Collected data encompassed patient demographics, specific disease indications, detailed endoscopic techniques employed, procedural success rates, and the incidence and management of related complications.ResultsThe study cohort had a mean age of 8.31 ± 3.63 years. The primary indication for ERCP was pancreatic disease, accounting for 72% (134/186) of procedures. These included chronic pancreatitis (n = 75), pancreatic trauma (n = 17), and acute pancreatitis with pseudocysts (n = 17). Biliary diseases constituted 28% (52/186), mainly choledocholithiasis (n = 33) and pancreatobiliary maljunction (n = 9). Commonly performed endoscopic interventions were pancreatic duct stent placement (n = 95), biliary stent placement (n = 50), and stone extraction from both ducts (n = 70 and 33, respectively). The overall procedural success rate was 90.5% (171/186). A significant difference was noted when stratified by operation time: procedures completed within 60 min had a 96.7% (115/119) success rate, compared to 80.0% (56/70) for those lasting 60 min or longer (P < 0.001). Post-procedure complications were recorded in 11 cases (5.9%), including post-pancreatitis (n = 6), infection (n = 4), and gastrointestinal bleeding (n = 1).All complications were all resolved with conservative medical management.ConclusionThis study confirms that pancreatic diseases (accounting for 72%) are the main indication. Endoscopic Retrograde Cholangiopancreatography (ERCP) has a high success rate (90.5%) in the diagnosis and treatment of biliary and pancreatic diseases in children. However, prolonged procedure time (>60 min) significantly reduces the success rate.